Occupational Accidents Among Healthcare Workers in Central Java - Nurmalia, Devi; Ulliya, Sarah; Sulisno, Madya; Ardani, Muhammad Hasib; Amilia, Rizqi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Healthcare workers have a risk of experiencing occupational accidents that may lead to injury or even death. Unavailable incident reporting can negatively impact the health and safety of healthcare workers and other larger sectors. This study aimed to investigate the occupational accidents among healthcare workers. A descriptive with a cross-sectional approach was conducted. This study involved 377 participants from five public and private hospitals in Central Java. Data were analyzed with the independent t-test and logistic regression. Healthcare workers generally experienced low occupational accidents. The most frequent incidents were: exposure to blood and body fluids (68.9%), sharp objects (50.4%), and needles (47.7%). Low rates of occupational accidents were significantly correlated with females (p=0.013). Healthcare workers experienced occupational accidents with various frequencies. Special attention to high frequent incidents is required and a more in-depth study on on the low-frequent.